2015
DOI: 10.1534/genetics.115.182808
|View full text |Cite
|
Sign up to set email alerts
|

A γ-Secretase Independent Role for Presenilin in Calcium Homeostasis Impacts Mitochondrial Function and Morphology in Caenorhabditis elegans

Abstract: Mutations in the presenilin (PSEN) encoding genes (PSEN1 and PSEN2) occur in most early onset familial Alzheimer's Disease. Despite the identification of the involvement of PSEN in Alzheimer's Disease (AD) 20 years ago, the underlying role of PSEN in AD is not fully understood. To gain insight into the biological function of PSEN, we investigated the role of the PSEN homolog SEL-12 in Caenorhabditis elegans. Using genetic, cell biological, and pharmacological approaches, we demonstrate that mutations in sel-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 79 publications
(122 reference statements)
9
94
0
Order By: Relevance
“…These Drp1 spirals will then constrict mitochondrial tubules through conformational changes, driven by GTP hydrolysis resulting in mitochondrial fission (Cereghetti et al, 2008;Cribbs and Strack, 2007;Xu et al, 2013). Mitochondrial morphological changes manifesting as fragmented mitochondria with damaged inner membrane structures have been observed in neurons in AD patients (Hirai et al, 2001) and consistent with this, mitochondrial structural disorganization has been observed in the body wall muscle and neurons of sel-12 mutants (Sarasija and Norman, 2015), suggestive of elevated Drp1 activity. Interestingly, ER-mediated calcium release and subsequent mitochondrial calcium uptake can impact the activity of Drp1 (Cereghetti et al, 2008;Cribbs and Strack, 2007;Xu et al, 2013).…”
Section: Calcium Homeostasis and Mitochondrial Function Is Disrupted supporting
confidence: 65%
See 4 more Smart Citations
“…These Drp1 spirals will then constrict mitochondrial tubules through conformational changes, driven by GTP hydrolysis resulting in mitochondrial fission (Cereghetti et al, 2008;Cribbs and Strack, 2007;Xu et al, 2013). Mitochondrial morphological changes manifesting as fragmented mitochondria with damaged inner membrane structures have been observed in neurons in AD patients (Hirai et al, 2001) and consistent with this, mitochondrial structural disorganization has been observed in the body wall muscle and neurons of sel-12 mutants (Sarasija and Norman, 2015), suggestive of elevated Drp1 activity. Interestingly, ER-mediated calcium release and subsequent mitochondrial calcium uptake can impact the activity of Drp1 (Cereghetti et al, 2008;Cribbs and Strack, 2007;Xu et al, 2013).…”
Section: Calcium Homeostasis and Mitochondrial Function Is Disrupted supporting
confidence: 65%
“…Using optogenetic, behavioral and pharmacological assays, it was demonstrated that there is increased ER-calcium signaling in sel-12 mutants (Sarasija and Norman, 2015) similar to what is observed in vertebrate systems with presenilin mutations (Chakroborty et al, 2009;Chan et al, 2000;Leissring et al, 2000a;Smith et al, 2005;Stutzmann et al, 2004;Tu et al, 2006). Calcium homeostasis is crucial for organismal health and therefore, mechanisms exist to ensure its maintenance.…”
Section: Calcium Homeostasis and Mitochondrial Function Is Disrupted mentioning
confidence: 55%
See 3 more Smart Citations